The effectiveness of commercial household ultraviolet C germicidal devices in Thailand - Pasita Palakornkitti (2022)
Ultraviolet C (UVC), or ultraviolet germicidal irradiation (UVGI), is known for its effective air, water, and surface disinfectant properties. With the rise of global awareness about public sanitation and personal hygiene due to the emergence of the current coronavirus disease 2019 pandemic, several applications of UVC were introduced to the commercial market. The present experimental study aimed to evaluate the effectiveness of commercial household UVC germicidal devices for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) inactivation. Ten UVC devices were included in the study comprising of 7 low-pressure mercury lamps (LPMLs) and 3 UVC- light-emitting diodes (LEDs). Considering applications, 3 were handheld UVGI surface disinfection equipment, 4 were UVGI disinfection chambers, and 3 were movable UVGI air and surface purifiers. To determine SARS-CoV-2 inactivation performance, UVC irradiance (mW/cm2) was measured 3 times repeatedly at distance and duration corresponding to manufacturers’ usage instructions. The required UVC dosage could not be achieved by either of UVC-LED devices (1 handheld UVGI surface disinfection equipment and 2 UVGI disinfection chambers). Five of seven LPMLs can sufficiently emit UVC irradiance for SARS-CoV-2-inactivation. A lack of standardization in the distance and cycle duration for each UVC application was observed. Standard usage guidelines for UVC devices are required to improve the effectiveness of UVC irradiance for SARS-CoV-2 inactivation as well as to minimize the potential side effects of UVC.